Role of the methionine cycle in the temperature‐sensitive responses of potato plants to potato virus Y. (4th November 2020) - Fesenko, Igor; Spechenkova, Nadezhda; Mamaeva, Anna; Makhotenko, Antonida V.; Love, Andrew J.; Kalinina, Natalia O.; Taliansky, Michael
Abstract: Plant–virus interactions are greatly influenced by environmental factors such as temperatures. In virus‐infected plants, enhanced temperature is frequently associated with more severe symptoms and higher virus content. However, the mechanisms involved in such regulatory effects remain largely uncharacterized. To provide more insight into the mechanisms whereby temperature regulates plant–virus interactions, we analysed changes in the proteome of potato cv. Chicago plants infected with potato virus Y (PVY) at normal (22 °C) and elevated temperature (28 °C), which is known to significantly increase plant susceptibility to the virus. One of the most intriguing findings is that the main enzymes of the methionine cycle (MTC) were down‐regulated at the higher but not at normal temperatures. With good agreement, we found that higher temperature conditions triggered consistent and concerted changes in the level of MTC metabolites, suggesting that the enhanced susceptibility of potato plants to PVY at 28 °C may at least be partially orchestrated by the down‐regulation of MTC enzymes and concomitant cycle perturbation. In line with this, foliar treatment of these plants with methionine restored accumulation of MTC metabolites and subverted the susceptibility to PVY at elevated temperature. These data are discussed in the context of the major function of the MTC in transmethylation processes. Abstract : The work describes mechanisms whereby proteomic, transcriptional, and metabolic changes associated with the methionine cycle may modulate temperature‐sensitive plant–virus interactions.